Insulin-loaded liposomes functionalized with cell-penetrating peptides: influence on drug release and permeation through porcine nasal mucosa - de Souza Von Zuben, Eliete [UNESP] (2021)
The nasal route is promising for the delivery of insulin for diabetes treatment. Drug loading into delivery systems such as liposomes can improve the bioavailability of insulin for this route. Herein, we address the development and characterization of insulin-loaded liposomes, functionalized with cell-penetrating peptides (CPPs), such as the TAT and Penetratin (PNT) peptides, which act as promoters of the penetration and absorption of the drug, and could further improve insulin bioavailability. Furthermore, it was evaluated the effect of both encapsulation and functionalization with CPPs on insulin release and permeation through the porcine nasal mucosa. The results obtained revealed that insulin-loaded liposomes functionalized with CPPs presented average values of hydrodynamic diameter in the nanometer scale, with low polydispersion index, and stable zeta potential, during the storage period of 90 days. Liposomes functionalized with CPPs at a concentration of 0.1 mM promoted a decrease in zeta potential values of − 49.6 ± 1.33 mV for insulin-loaded liposomes to − 33.9 ± 1.10 mV when functionalized with TAT and − 20.6 ± 1.30 mV when functionalized with PNT owing to electrostatic interaction between highly positively charged CPPs and negatively charged insulin. Insulin encapsulation with non-functionalized liposome was 72%, but when functionalized with PNT and TAT, it decreased, respectively to 60% and 71%. Photomicrographs obtained by transmission electron microscopy showed a small multilamellar and unilamellar morphology and in nanometric scale (80–150 nm). The spectra of circular dichroism carried out in all formulations demonstrated that the integrity and stability of the insulin were preserved, as observed in the insulin in solution. In vitro release kinetics of insulin from liposomes followed Weibull's mathematical model, which relates the amount of drug accumulated in solution as a function of time. Comparing the systems, it was verified that the addition of CPPs in the formulations decreased permeation through the porcine nasal mucosa, because of electrostatic interaction between insulin and CPPs, which in turn, may be inhibiting the peptide's absorption-promoting activity. Therefore, when associated with liposomes, penetratin and TAT peptides did not show evidence of increasing insulin permeation through the nasal mucosa. However, insulin-loaded liposomes without functionalization with CPPs increased nasal permeability coefficient, suggesting that the developed system can optimize the absorption of insulin through the nasal route, which has not been previously published.